성취만족도에 대한 탐색적 연구 : 코로나19 전후, 주거점유 형태, 교육 정도에 따른 차이를 중심으로 - 기은광; 조민식 (사회적질연구, 5(4), 2021)
본 연구는 ‘인생에서 사회경제적으로 성취한 것에 대한 만족도’를 의미하는 사회적․경제적 성취만족도(협의의 성취만족도)를 다루고 있다. ‘성취동기’는 성취를 이끌어 내는 데에 초점을 두고 있는데 비해, ‘성취만족도’는 성취에 대한 개인적인 평가와 의미에 초점을 두는 개념이다. 성취만족도는 성취와 성취동기의 상호작용에 있어서 연결고리의 역할을 하며 성취와 성취동기에 대한 입체적 분석을 가능케 한다. 또한, 성취만족도는 사회인구학적 변수들(소득, 재산, 학력 등)이 생활만족도나 성평등 등에 미치는 영향을 분석할 때에도 매개적 역할을 할 것으로 기대되는 변수이다. 이런 효용에도 불구하고 아직 성취만족도에 대한 학술적 차원의 연구가 많지 않은 상황이다. 이에 본 연구는 성취만족도를 실증적으로 탐색하기 위한 연구를 진행하였다. 본 연구는 통계청에서 진행한 2018~2020 년 사회조사 데이터를 활용하였으며, 만 19세 이상의 성인 35,331명을 대상으로 하였다. 기술적 분석과 t-test, ANOVA를 사용하여 데이터를 분석하였다. 본 연구의 연구결과, 성취만족도는 성별·연 령집단 내에서 코로나19 전후로 차이를 보였고, 주거점유 형태에 따라서도 차이를 보였으며, 또한 교육정도에 따라서도 차이를 보였다. The achievement satisfaction discussed in this study is the achievement satisfaction of consultation and social and economic achievement satisfaction. The achievement satisfaction is expected to serve as a link between achievements, achievement motivation, and life satisfaction. This study is to empirically explore the concept of achievement satisfaction. This study utilized the data from the 2018, 2019 and 2020 social surveys conducted by the Statistics Korea and targeted 35,331 adults aged 19 or older. For the data analysis, technical analysis, t-test, and ANOVA were used. The research results are as follows. The analysis revealed that there were differences in achievement satisfaction within the gender age group among the data from 2018, 2019 and 2020. The study examined whether there were differences according to genders in achievement satisfaction and found that differences were mainly noticeable in the elderly. It also examined whether types of occupancy affected achievement satisfaction and found differences in achievement satisfaction by types of occupancy among men in the 25-29 years old group to 65 years old or older group, and women in the 30-34 years old group to 65 years old or older group. There was a clear difference in achievement satisfaction between groups depending on the levels of education. There was a consistent difference in achievement satisfaction according to the levels of education. KCI Citation Count: 0